Coarse particulate matter and airborne endotoxin within wood stove homes. (18th April 2013) - McNamara, M.; Thornburg, J.; Semmens, E.; Ward, T.; Noonan, C.
Abstract: Emissions from indoor biomass burning are a major public health concern in developing areas of the world. Less is known about indoor air quality, particularly airborne endotoxin, in homes burning biomass fuel in residential wood stoves in higher income countries. A filter‐based sampler was used to evaluate wintertime indoor coarse particulate matter (PM10‐2.5 ) and airborne endotoxin (EU/m 3, EU/mg) concentrations in 50 homes using wood stoves as their primary source of heat in western Montana. We investigated number of residents, number of pets, dampness (humidity), and frequency of wood stove usage as potential predictors of indoor airborne endotoxin concentrations. Two 48‐h sampling events per home revealed a mean winter PM10‐2.5 concentration (± s.d.) of 12.9 (± 8.6) μg/m 3, while PM2.5 concentrations averaged 32.3 (± 32.6) μg/m 3 . Endotoxin concentrations measured from PM10‐2.5 filter samples were 9.2 (± 12.4) EU/m 3 and 1010 (± 1524) EU/mg. PM10‐2.5 and PM2.5 were significantly correlated in wood stove homes ( r  = 0.36, P  < 0.05). The presence of pets in the homes was associated with PM10‐2.5 but not with endotoxin concentrations. Importantly, none of the other measured home characteristics was a strong predictor of airborne endotoxin, including frequency of residential wood stove usage.